Rekonstruksi Konsep Tamkin Sempurna dalam Pasal 80 Ayat (5) KHI Perspektif Maqasid Abdullah bin Bayyah - Fashihuddin, Muhammad; Sj, Fadil; Izzuddin, Ahmad (Fakultas Syariah INSURI Ponorogo, 2023)
The Compilation of Islamic Law is the material basis for the Panel of Judges in deciding cases in the Religious Courts. However, the substantive content of KHI still needs to be reviewed. One of them is the problem of perfect tamkin as the cause of the husband's obligation to support his wife in Article 80 paragraph (5) KHI. The meaning contained in this phrase is classified as abstract, thus giving birth to various interpretations of judges, even though in essence the cases handled tend to be the same. Therefore, this study aims to determine substantive weaknesses and reconstruct the meaning of perfect tamkin and review it from Abdullah bin Bayyah's maqasid perspective. The method used is normative qualitative method using KHI as the primary legal material. Methods of data collection using the method of documentation. This research resulted in: (1) in article 80 paragraph (5) KHI found substantive weaknesses that must be addressed, namely: a) incomplete adoption of fiqh opinions; b) the substance of the article which leads to the applicability of meaning in general; and c) the judges' interpretations vary which causes confusion in the meaning of nature. (2) in reconstructing the article, elaboration is needed between the interpretation of the fuqaha and the judge. In order to find a formula regarding the definition of perfect tamkin, its indicators, and the conditions for a wife to earn a living. In the maqasid review, it was found that the method used to determine tamkin is sukut al-syari' and it belongs to al-wasilah ila al-maqsad al-tabi'i